Wary tuberculosis and cholestatic type hepatitis. A case report - Edi Hartoyo Edi Hartoyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Tuberculosis is still a major health problem in Indonesia. The organ commonly affected is lung (pulmonary tuberculosis) but other organs (extrapulmonary tuberculosis) may also be involved. Working diagnosis of tuberculosis in childhood is usually established by tuberculin test, chest x-ray and clinical manifestations, but it is often difficult to establish diagnosis of childhood tuberculosis as the chest x-ray and clinical manifestations are not always specific and we have difficulty in finding tuberculosis such as scoring method, bactec, serologic examination and biomolecular technic. However all of those examinations require further study for practical clinical use in the future. We report 12 year old child suffering from miliary tuberculosis and cholestatic type hepatitis. The recommended treatment for miliary tuberculosis is INH 10 mg/kgbw/day, Rifampicin 15 mg/kgbw/day, Ethambutol 15 mg/kgbw/day, Pyrazinamid 20 mg/ kgbw/day (for 2 months). Thereafter, the therapy was continued according to the conventional protocol. For the cholestatic type hepatitis we gave ursodeoxycolic (urdafalk) 8 mg/kgbw/day and cursil 2 x 1. The patient's condition improved after evaluation of 3 week therapy.Key words: miliary tuberculosis - diagnostic problem - cholestatic hepatitis - management